Fifteen hypothesis on genres to delatate shortstory - Mateos Blanco, Belén (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
This work aims to reveal the generic identity of the microstory from the postulates of Alberto Vital in Fifteen hypotheses on genres (2012). The axioms of the Mexican diverge from the traditional study that confines his analysis to the discursive, formal, thematic and pragmatic characteristics. Vital presents a method of diagnosis and evaluation whose tools try to justify the concept of literary genre according to the incidence and relation of this with man: his history, his culture, his needs and vital moments, his role in the society that inhabits ...